1973
DOI: 10.1021/ja00785a011
|View full text |Cite
|
Sign up to set email alerts
|

Formation, reactivity, and relative stability of clustered alkoxide ions by cyclotron resonance spectroscopy

Abstract: Ion cyclotron resonance spectroscopy has been used to study the general gas-phase reaction of alkoxide ions (RBO-) with alkyl formates (HCOORb) for R = CH3, C&, and i-CbHT. These systems are shown to lead in all cases to the formation of a complex ion, (R,Rb02H)-, and to produce alkoxide displacement (RbO-) only when the electron affinity of RbO . is equal to or larger than that of R,O.. Evidence is presented that the complex ions correspond to alkoxide ions "solvated" by a single neutral molecule of alcohol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…The product R O -+ (CH,),CCONH, -+ (CH,),CCOOR' -(CH,),CCONH-+ R'OH (8)(CH,),CCOO-+ R'NHL( 9 ) (or olefin + NH3) (M-1)-+ NH, R = CF3, C H 3 0 , C2H50 Alkyl pivalates display a much more complex reactivity pattern as described in the set of reactions 7-10.…”
mentioning
confidence: 99%
“…The product R O -+ (CH,),CCONH, -+ (CH,),CCOOR' -(CH,),CCONH-+ R'OH (8)(CH,),CCOO-+ R'NHL( 9 ) (or olefin + NH3) (M-1)-+ NH, R = CF3, C H 3 0 , C2H50 Alkyl pivalates display a much more complex reactivity pattern as described in the set of reactions 7-10.…”
mentioning
confidence: 99%
“…Charge-localized ions reacted to give mainly ␣-elimination, whereas chargedelocalized ions reacted exclusively at the carbonyl group. Pioneering work by Riveros and co-workers 15,16 on alkyl formate reactions with alkoxides and by Johlman and Wilkins 17 on hydroxide-alkyl formate systems showed that when different pathways are available, ␣-elimination is a major pathway. Brickhouse and Squires 6 have also shown that there are significant differences in the reactivity of charge localized and delocalized ions with 6,6-dimethylfulvene.…”
Section: Proton Transfer Vs Transacylationmentioning
confidence: 99%
“…Although the Riveros reaction, equation (1), is the major reaction pathway for methoxide, 11,15,16 Table 1 shows that in the reaction between benzyl anion and various formates, no S N 2 or Riveros reaction products were observed. For ethyl and especially tert-butyl formate, we observe secondary Riveros reaction products:…”
Section: Proton Transfer Vs Transacylationmentioning
confidence: 99%
“…The same applies to substitutions with phenyl [5,6] and trifluoromethyl groups. [7,8] Experimental results are given below. This work is aimed at getting new experimental information by means of Fourier Transform ICR (FT-ICR) [9][10][11][12][13][14][15][16][17] and computational data on the eventual additivity of these effects as well as to determine under the same experimental conditions the effect of multiple phenyl substitutions.…”
Section: Introductionmentioning
confidence: 99%